ADMINISTRATIVE FACTORS AFFECTING THE PERFORMANCE OF INTERNAL QUALITY ASSURANCE IN SCHOOLS UNDER CHONBURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Tingtang, Palita; Narkpoy, Linda; Onkasem, Porntip (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
The purposes of this research were to 1) examine the level of administrative factors, 2) identify the operational level of internal quality assurance in schools, 3)determine the relationship between administrative factors and the operational level of internal quality assurance in schools, and 4) examine the administrative factors affecting the operation of internal quality assurance in schools under Chonburi Primary Educational Service Area Office 2. The research sample consisted of 302 participants, including school administrators and teachers, obtained from Krejci and Morgan's table, and a multistage sampling. The instrument used for data collection was a set of questionnaires, with the reliability of 0.99. The statistics for data analysis were frequency, percentage, mean, standard deviation, Pearson’s product-moment correlation coefficient, and multiple regression analysis. The research results revealed that: 1) The administrative factors, as a whole and in each aspect, was at a high level, ranking by mean scores ​​from high to low, including organizational culture, leadership, personnel, media and information technology, and environment, respectively; 2) The operation of internal quality assurance in schools, as a whole, was at a high mean score level. When ranking by mean scores ​​from high to low, including operations based on the educational development plans, preparation of educational development plans, preparation of self-assessment reports, operational monitoring, formulation of educational standards, and educational quality evaluation and auditing, respectively; 3) The administrative factors and the operation of internal quality assurance in schools showed a high level of positive relationship at the .01 level of significance; and 4) The administrative factors affecting the operation of internal quality assurance in schools were arranged in order of predictive power, from highest to lowest, as follows: organizational culture, personnel, leadership, media and information technology, and environment. These aspects could jointly predict the quality assurance operation in schools at 79.60 percent and were able to formulate a predictive equation based on standardized scores as Z´Y = .393Z5 + .284Z2 + .236Z4 + .194Z3 + .180Z1.